2016
DOI: 10.3233/wor-162327
|View full text |Cite
|
Sign up to set email alerts
|

The effect of work motivation on a sample of nurses in an Italian healthcare setting

Abstract: Practical implications for organizations and employees are discussed along with a call for further research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 54 publications
4
17
1
Order By: Relevance
“…Findings show that perceived organizational support has a significant and positive effect on organizational commitment. These findings support the current literature (Settoon et al, 1996;Eisenberger et al, 2001;Yoon and Thye, 2002;Allen et al, 2003;Özdevecioğlu, 2003;Bishop et al, 2005;Makanjee et al, 2006;Piercy et al, 2006;Zhang et al, 2012;Altınöz et al, 2013;Ersoy, 2014;Galletta et al, 2016;Afif, 2018;Karadirek, 2020). Also, it was concluded that perceived organizational support had a significant and positive effect on emotional, normative and continuation commitment.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Findings show that perceived organizational support has a significant and positive effect on organizational commitment. These findings support the current literature (Settoon et al, 1996;Eisenberger et al, 2001;Yoon and Thye, 2002;Allen et al, 2003;Özdevecioğlu, 2003;Bishop et al, 2005;Makanjee et al, 2006;Piercy et al, 2006;Zhang et al, 2012;Altınöz et al, 2013;Ersoy, 2014;Galletta et al, 2016;Afif, 2018;Karadirek, 2020). Also, it was concluded that perceived organizational support had a significant and positive effect on emotional, normative and continuation commitment.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Hypothesis 1b has not been confirmed. These results are generally supported by the literatüre (Tremblay, Gaudet and Vandenberghe, 2019;Hong, Jeong and Downward, 2019;Hsieh, Wang and Huang, 2019;Afif, 2018;Galletta et al, 2016;Kurtessis et al, 2015;Gillet et al, 2013;Miao, 2011;Gagné et al, 2010;Riggle, Edmondson and Hansen, 2009;Özdevecioğlu, 2003;Rhoades and Eisenberger, 2002;Eisenberger et al, 2001;Armeli et al, 1998;Eisenberger et al, 1997).…”
Section: Extended Summary Introductionsupporting
confidence: 54%
“…Previous research supports the idea that organizations benefit from creating working environments that promote intrinsic motivators. Promotion of intrinsic motivators includes focusing on the meaningfulness of work, on personal mastery, on providing positive feedback, on opportunities to learn new things, and contributing to quality improvement …”
Section: Discussionmentioning
confidence: 99%